2018
DOI: 10.12816/0051131
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance on the Financial, Governance and Social Disclosure at Islamic Banks in Malaysia

Abstract: The study examines the impact of board and audit committee on the disclosure of Islamic financial and social reporting (IFSR) among Islamic banks in Malaysia. Drawing on surveys this study seeks the views of accountants working in Islamic banks regarding the importance of items in the IFSR index developed by Marsidi et al. (2016). The annual reports are thereafter used to examine the score of the IFSR for the Islamic banks as well as to collect the data for the related variables. The multivariate regression fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…This outcome considered that with elevated governance, whether the institution's performance is poor, the IBs would be committed to conforming to accounting disclosure. The positive power of governance on the FD is consistent with Marsidi et al (2018). This positive association is explicated by the presence of governance, which helps the bank to increase the disclosure standards and to issue protection for shareholders' interests.…”
Section: Empirical Findingssupporting
confidence: 60%
See 1 more Smart Citation
“…This outcome considered that with elevated governance, whether the institution's performance is poor, the IBs would be committed to conforming to accounting disclosure. The positive power of governance on the FD is consistent with Marsidi et al (2018). This positive association is explicated by the presence of governance, which helps the bank to increase the disclosure standards and to issue protection for shareholders' interests.…”
Section: Empirical Findingssupporting
confidence: 60%
“…It is assumed that IBs with higher board scores should have an effective BOD structure. Marsidi et al (2018) explored the impact of the BOD on financial disclosure (FD) in Malaysia by analyzing 48 annual reports for 12 IBs from 2007 to 2010 and found a significant relationship. This finding signifies that the board needs to secure the carried-out stakeholders' activities.…”
Section: 24mentioning
confidence: 99%
“…The study of Isa and Muhammad (2015) also conclude board size is an important factor for voluntary disclosure where larger board size viewed as having more expertise as compared to smaller board. Further, Marsidi et al (2018) suggests that board size is a significant factor to explain the financial and social disclosure among Malaysian Islamic banks. The results of Matuszak et al (2019) also found that board size has a positive significant effect on corporate social related reporting.…”
Section: Board Sizementioning
confidence: 99%
“…Because of the specificity of IBs, the AC’s members should have a sound knowledge of the IB’s business environment and industry to achieve AC’s responsibility, and therefore, improve the compliance with AAOIFI’s standards. To our knowledge, only Abdullah et al (2015a, 2015b) and Marsidi et al (2018) have examined the relationship between AC expertise and voluntary disclosure of IBs. Indeed, Marsidi et al (2018) found an insignificant association between AC expertise and voluntary disclosure for IBs in Malaysia.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…To our knowledge, only Abdullah et al (2015a, 2015b) and Marsidi et al (2018) have examined the relationship between AC expertise and voluntary disclosure of IBs. Indeed, Marsidi et al (2018) found an insignificant association between AC expertise and voluntary disclosure for IBs in Malaysia. However, Abdullah et al (2015a, 2015b) proved that AC financial expertise is positively associated with voluntary CG disclosures of IBs in Southeast Asia and the GCC region.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%